Case report: Use of granulocyte-colony stimulating factor as an immunomodulatory therapy in a patient with neuromyelitis optica spectrum disorder and comorbid immunodeficiency - Perez Giraldo, Gina S.; Graham, Edith L.; VanHaerents, Stephen; Balabanov, Roumen (Frontiers in Neurology, 2023)
Background Autoimmune diseases can coexist with immunodeficiency. We describe a treatment approach in which granulocyte-colony stimulating factor (G-CSF) is used to restore immune competence without worsening autoimmunity. G-CSF is a polyfunctional cytokine that influences survival, proliferation, and differentiation of hematopoietic stem cells, and has immunomodulatory effects on the innate and adaptive immune systems. Objective To report a case of neuromyelitis optica spectrum disorder (NMOSD) with comorbid immunodeficiency and frequent infections. Methods Case report and review of literature. Results A 23 years-old man presented with a focal onset seizure with impaired awareness at age 12. At age 18, he developed headaches, recurrent multifocal seizures, and non-convulsive status epilepticus. Brain magnetic resonance imaging (MRI) showed extensive T2 hyperintense and gadolinium-enhancing periventricular and corpus callosum lesions. Serum aquaporin 4 antibody was positive 1:10,000 (normal value <1.5 titer), hence he was diagnosed with NMOSD. As a complication, patient developed mucormycotic pneumonia with cavitation, requiring thoracotomy precluding use of immunosuppressants. Gene testing demonstrated a mutation in MT-ND4 gene encoding for NADH dehydrogenase 4 in mitochondrial complex 1. Eventually, he began a treatment with filgrastim, a G-CSF analog, in addition to intravenous immunoglobulins and prednisone. Patient’s NMOSD has been in remission without relapses, or coexistent infections ever since. Conclusion G-CSF is a polyfunctional cytokine with important immunomodulatory effects, which makes it an interesting therapeutic option when autoimmunity coexists with immunodeficiency and was used successfully in this case.